THE NARRATIVE CONSTRUCTION OF FREUDIAN GUILT IN OPPENHEIMER (2023) - Irsyad Rauhillah Fa'iz; Evangeline G. Luna; Davin Zachary Yassa; Ghalib Amri Musyafa (Saksama: Jurnal Sastra, 2026)
This study examines the representation of guilt in Christopher Nolan’s film Oppenheimer (2023) by synthesizing David Bordwell’s narratological framework with Sigmund Freud’s structural model of psychoanalysis. Rather than offering a clinical diagnosis or analyzing the film as an objective historical biography, this research treats the work as a formal narrative construct where non-linear temporal reordering directly mirrors the protagonist's internal psychic fragmentation and moral decay. Using a qualitative-descriptive methodology, the paper conducts a detailed textual analysis of selected scenes, cinematic devices, and mise-en-scène to examine how the reordering of the syuzhet (plot) relative to the chronological fabula (story) functions as a cinematic metaphor for the dynamic tension between the Id, Ego, and Superego. The analysis reveals that the film's narrative architecture systematically maps Oppenheimer’s psychological deterioration. Specifically, the color-saturated Fission timeline and early impulsive acts foreground the unchecked intellectual drives of the Id. The logistical orchestration of the Manhattan Project and the Trinity Test depict the pragmatic mediation of the Ego, which ultimately weakens under overwhelming historical pressures. Finally, the black-and-white Fusion timeline, non-linear fragmentation, and subjective hallucination sequences embody the punitive, sadistically aggressive nature of the Superego, trapping the protagonist in chronic melancholia and unassimilated remorse. The study concludes that Nolan’s non-linear narrative structure is an artistic tool where cinematic form enacts psychoanalytic depth, projecting Oppenheimer's inescapable guilt and the structural collapse of the self.